2016
DOI: 10.1093/europace/euw032
|View full text |Cite
|
Sign up to set email alerts
|

Different impact of long-detection interval and anti-tachycardia pacing in reducing unnecessary shocks: data from the ADVANCE III trial

Abstract: AimsA long-detection interval (LDI) (30/40 intervals) has been proved to be superior to a standard-detection interval (SDI) (18/24 intervals) in terms of reducing unnecessary implantable cardioverter defibrillator (ICD) therapies. To better evaluate the different impact of LDI and anti-tachycardia pacing (ATP) on reducing painful shocks, we assessed all treated episodes in the ADVANCE III trial.Methods and resultsA total of 452 fast (200 ms < cycle length ≤ 320 ms) arrhythmic episodes were recorded: 284 in 138… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…A longer cycle length of the ventricular arrhythmias, has been identified as predictors for successful ATP therapy in some prior studies . However, in this cohort, cycle length did not differ between successful and unsuccessful ATP attempts.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…A longer cycle length of the ventricular arrhythmias, has been identified as predictors for successful ATP therapy in some prior studies . However, in this cohort, cycle length did not differ between successful and unsuccessful ATP attempts.…”
Section: Discussionmentioning
confidence: 50%
“…In one case, an inappropriate ATP delivered during AF induced a VT, which was terminated by a shock. Contemporary programming allows for longer detection times resulting in less inappropriate therapy, but exact impact is not well studied . However, one can expect a reduction in these numbers as the total number of ATP therapy episodes is reduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…56,57 These studies had a significant impact on ICD programming strategies, and spawned a number of similar studies examining variations on lenient programming practices. Several studies have examined high rate programming, 58,59 while others have considered prolonged detection, [60][61][62][63][64][65] or a combination of these two approaches. 66,67 In general, lenient programming practices in these studies have demonstrated a decrease in the rate of appropriate and inappropriate shocks, with either a decrease in overall mortality or no difference, when compared to conventional programming practices.…”
Section: Device-based Interventions-data From Studies In Adult Patientsmentioning
confidence: 99%